Synthesis of 2D Porous Crystalline Materials in Simulated Microgravity. Issue 30 (4th June 2021) - Contreras‐Pereda, Noemí; Rodríguez‐San‐Miguel, David; Franco, Carlos; Sevim, Semih; Vale, João Pedro; Solano, Eduardo; Fong, Wye‐Khay; Del Giudice, Alessandra; Galantini, Luciano; Pfattner, Raphael; Pané, Salvador; Mayor, Tiago Sotto; et al.
Abstract: To date, crystallization studies conducted in space laboratories, which are prohibitively costly and unsuitable to most research laboratories, have shown the valuable effects of microgravity during crystal growth and morphogenesis. Herein, an easy and highly efficient method is shown to achieve space‐like experimentation conditions on Earth employing custom‐made microfluidic devices to fabricate 2D porous crystalline molecular frameworks. It is confirmed that experimentation under these simulated microgravity conditions has unprecedented effects on the orientation, compactness and crack‐free generation of 2D porous crystalline molecular frameworks as well as in their integration and crystal morphogenesis. It is believed that this work will provide a new "playground" to chemists, physicists, and materials scientists that desire to process unprecedented 2D functional materials and devices. Abstract : How to achieve simulated microgravity conditions on Earth? The art of growing and processing 2D porous crystalline molecular frameworks in simulated microgravity is presented.